2018
DOI: 10.1101/276196
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Non-canonical Wnt signalling initiates scarring in biliary disease

Abstract: Cholangiopathies, or biliary diseases, account for a significant proportion of adult and paediatric liver disease. In these pathologies, iterative cycles of damage and repair result in the development of a regenerative microenvironment surrounding the bile ducts, which orchestrates both epithelial proliferation and also biliary fibrosis. Ultimately, fibrosis at the cost of repair results in cholestasis and liver failure, necessitating liver transplantation. Whilst the fibrogenic mechanisms in hepatocellular di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 70 publications
0
1
0
Order By: Relevance
“…Similarly, the level of Mapk8 is increased after ductular lineage commitment and during ductular morphogenesis (Figure 5E). In the adult regenerating bile duct JNK signalling is lost following functional Vangl2 -loss 37 similarly, in FLOs the levels of pJNK T183/Y185 are significantly decreased (Figure 5F). Furthermore, when we specifically look for levels of RHOC we found that this is significantly reduced in FLOs derived from Vangl2 S464N mutant mice (Figure 5G).…”
Section: Resultsmentioning
confidence: 78%
“…Similarly, the level of Mapk8 is increased after ductular lineage commitment and during ductular morphogenesis (Figure 5E). In the adult regenerating bile duct JNK signalling is lost following functional Vangl2 -loss 37 similarly, in FLOs the levels of pJNK T183/Y185 are significantly decreased (Figure 5F). Furthermore, when we specifically look for levels of RHOC we found that this is significantly reduced in FLOs derived from Vangl2 S464N mutant mice (Figure 5G).…”
Section: Resultsmentioning
confidence: 78%